PENGARUH INTELLIGENCE QUOTIENT (IQ) TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA BANK RAKYAT INDONESIA UNIT PASIR PENGARAIAN 1 )â€ - .NST, NURRAHMI. AS (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
Human Resourcesis avery important elementfor any company, because thesuccessor failure of a company depend sonits human resources. Every company Islooking for people who are high IQ, with the hope of getting a qualified work force thatcaneventually bring the company to abetter direction. This study aimsto determine theeffect ofEffect of Int elligence Quotient (IQ) on the performance of employees of the BankRakyat Indonesia(BRI) Pengaraian Sand Unit 1 Total population of 25 people andthetechnique of sample censustechniques. In this study, the data used are primary dataand secondary data analysis technique used is a simple linear regression and hypothesistesting using the T-test test test and correlation coefficientand coefficient ofdetermination.Regression Y=34.114+0.824X of this study it can be concluded that basedon the statistical test that the variable Intelligence Quotient(IQ) effect on performance.From this study adjusted R2 values obtained for 0.599, it means that 59.9% of employeesaffect the performance IQ